Cardiovascular Safety of Stimulants in Children with Attention-Deficit/Hyperactivity Disorder: A Nationwide Prospective Cohort Study - Dalsgaard, Søren (Mary Ann Liebert, Inc., 2014)
Objective: The purpose of this study was to determine whether stimulant users are at higher risk of a later cardiovascular event than are non-users, examining this association in both a national cohort and a population-based sample of children and adolescents diagnosed with attention-deficit/hyperactivity disorder (ADHD). We also aim to examine a possible dose-response relationship in such an association. Methods: We conducted a longitudinal, prospective cohort study of all children born in Denmark between 1990 and 1999. Within this cohort, children with ADHD were identified. Data from national health registers on psychiatric and somatic diagnoses, stimulant prescriptions, cardiovascular risk factors, pre- and perinatal and sociodemographic covariates in all children and their parents were merged, using the unique personal identification number. Hazard ratios (HR) for cardiovascular events were estimated using Cox regression, adjusted for other known risk factors. Results: In the total population (n=714,258 contributing a total of 6,767,982 person-years) use of stimulants increased the risk of a cardiovascular event; adjusted HR=1.83 (1.10–3.04). In children with ADHD (n=8300) stimulant treatment also increased the risk of a cardiovascular event (adjusted HR=2.20 [2.15–2.24]), with a complex time-dependent dose-response relationship. Conclusions: This is the first nationwide cohort study of the cardiovascular safety of stimulants in children and adolescents, and it represents, to our knowledge, the longest prospective follow-up study. Cardiovascular events were rare but twice as likely in stimulant users as in non-users, both in the total national population and in children with ADHD. We found a complex, time- and dose-dependent interrelationship between cardiovascular adverse events and stimulant treatment in children and adolescents. Our results suggest a safety signal with an increased risk of cardiovascular disease associated with stimulant treatment in children and adolescents, even after adjusting for a number of potential confounders.